Analisis Faktor yang Mempengaruhi Produktivitas dan Kesejahteraan Petani Kopi di Indonesia - Heppi Syofya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to see what factors affect the productivity and welfare of coffee farmers in Indonesia. The data analysis method used to calculate all the data that has been obtained using multiple linear regression analysis with the help of SPSS. This study shows the factors that affect the productivity of coffee farmers, namely capital, labor, land area, technology and experience. Based on the results of the analysis, 5 variables of capital, labor, land area, technology, and farming experience were found simultaneously, influencing the productivity and welfare of coffee farmers in Indonesia.